Perancangan Sistem Kendali dan Monitoring Tegangan Motor 3 Fasa Berbasis Internet of Things Menggunakan Aplikasi Blynk - Supono, Tri Rijanto, Jati Widyo Leksono (Universitas Hasyim Asy'ari, 2020)
Internet of Things is a technological development that must be followed along with the development of the era and revolution of the 4.0 industry today. With the Internet of Things can work more efficiently and effectively wherever we are like CCTV monitoring process, smarthome and 3 phase motor voltage monitoring. The purpose of this research is to control system switch on off and monitor the Internet of Things 3-phase motor voltages. This research is an experimental study by controlling the on off control system which is controlled from the Blynk application and monitoring the reading results of the ZMPT101B voltage sensor which measures the phase voltages R, S, and T whose results are sent by the ESP32 module to be displayed on a smartphone using the blynk application. This research uses the method measurement of voltage values not only relies on sensor readings, but also uses an AVOmeter with the aim of measuring the accuracy of sensor readings. From sensor readings and AVOmeter measurements, it will be compared to its value by knowing a percentage of error values from both measuring instruments. From the test results obtained an average time of 12.6 seconds for control on and 15.6 seconds for control off as well results in a motor voltage error value I phase R = 0.98%, S = 1,1%, T = 0,8% and motor II phase R = 2,1%, S = 2%, T = 1%. The average motor voltage using the AVOmeter gauge for motor I of R = 233.1 V, S = 234 V, T = 232.5 V, motor II phase R = 233.1 V, S = 233.6 V, T = 233 V, while the voltage sensor gauge ZMPT101B motor I average of R = 230.8 V, S = 231.4 V, T = 230.7 V, and phase II motor R = 228.2 V, S = 228.7 V, T = 230.2 V.